Transformation of Local Cultural Values in the Lives of the Young Generation: The Influence of Globalization and Urbanization - Djumat, Irwan; Lalihun, Ishaka; Haulussy, Rais Rahman; Yaurwarin, Wahid (Socious Journal, 2025)
The transformation of local cultural values in the lives of young people is becoming an increasingly relevant issue in the midst of rapid globalization and accelerated urbanization. This article aims to examine how these two major forces affect the understanding, appreciation, and practice of local cultural values among the younger generation. Globalization brings popular culture, information technology and transnational lifestyles that often conflict with traditional values such as collectivity, respect for customs and emotional attachment to local communities. Meanwhile, urbanization creates a social environment that tends to be anonymous, competitive and pragmatic, thus diminishing the role of traditional social environments as guardians of cultural values. Through an in-depth literature study, this article finds that young people in various parts of Indonesia experience a complex process of cultural identity negotiation. On the one hand, they are exposed to modern values that promise progress and social mobility, but on the other hand, they still have cultural ties inherited by family and community. This transformation process is not linear, but rather shows a pattern of selective adaptation that can open up opportunities for the revitalization of local culture in a new format that is more contextual and relevant. With a reflective and participatory approach, education based on local culture and digital media can be an important tool in bridging traditional values with the dynamics of modern life of the younger generation